Dual Labour Markets and (Lack of) On-the-Job Training: PIAAC Evidence from Spain and Other EU Countries - Antonio Cabrales; Juan J. Dolado; Ricardo Mora (Institute for the Study of Labor (IZA), 2014)
Using the Spanish micro data from the Programme for the International Assessment of Adult Competencies (PIAAC), we first document how the excessive gap in employment protection between indefinite and temporary workers leads to large differentials in on-the-job training (OTJ) against the latter. Next, we find that that the lower specific training received by temporary workers is correlated with lower literacy and numeracy scores achieved in the PIAAC study. Finally, we provide further PIAAC cross-country evidence showing that OJT gaps are quite lower in those European labour markets where dualism is less entrenched than in those where it is more extended.
Keywords: C14; C52; D24; J24; 330; dual labour market; on-the-job training; cognitive skills; severance pay